2014
DOI: 10.1074/jbc.m114.548677
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal-induced Metallothionein Expression Is Regulated by Specific Protein Phosphatase 2A Complexes

Abstract: Background:The molecular mechanism and key signaling pathways underlying MT expression in response to metal stress remains elusive. Results: Upon metal stress, PP2A PR110 complexes bind to and dephosphorylate MTF-1 at Thr-254, leading to the transactivation of MTs. Conclusion: Specific PP2A complexes regulate metal-induced MTs expression. Significance: Delineate a novel pathway regulating metal-induced cytotoxicity and clarify the role of PP2A in cellular stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 59 publications
(59 reference statements)
2
32
0
Order By: Relevance
“…To create stable AML-12 and HepG2 cells expressing shRNAs against PP2A A␣ or B subunit, pLKO-shRNAs (14) were introduced into AML-12 or HepG2 cells by lentiviral infection and selected with puromycin (1 g/ml). For the induction of Cyp2e1 expression, HepG2 cells were seeded in 6-cm plates with a density of 8 ϫ 10 5 and treated with three types of Cyp2e1 agonists for 24 h. The chemicals and their concentrations were: ethanol (0, 100, 200, and 400 mM), acetaminophen (0, 1.25, 2.5, and 5 M), and hydroquinone (0, 6.25, 12.5, and 25 M).…”
Section: Stable Cell Line Establishment and Cell Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To create stable AML-12 and HepG2 cells expressing shRNAs against PP2A A␣ or B subunit, pLKO-shRNAs (14) were introduced into AML-12 or HepG2 cells by lentiviral infection and selected with puromycin (1 g/ml). For the induction of Cyp2e1 expression, HepG2 cells were seeded in 6-cm plates with a density of 8 ϫ 10 5 and treated with three types of Cyp2e1 agonists for 24 h. The chemicals and their concentrations were: ethanol (0, 100, 200, and 400 mM), acetaminophen (0, 1.25, 2.5, and 5 M), and hydroquinone (0, 6.25, 12.5, and 25 M).…”
Section: Stable Cell Line Establishment and Cell Treatmentmentioning
confidence: 99%
“…Reversible protein phosphorylation mediated by protein kinase and phosphatase plays a critical role in the regulation of many cellular processes in eukaryotes. Dysregulation of protein phosphorylation can be triggered by environmental pollutants, thus mediating toxic effects (13,14). Prior studies have shown that benzene and its metabolites may activate several key signaling pathways such as PI3K-AKT, p38 MAPK, or JNK, subsequently triggering apoptosis of marrow cells or malignant progression of human leukemia cells (15,16), suggesting the involvement of protein kinase in benzene-induced toxicity.…”
mentioning
confidence: 99%
“…While direct and reversible activation of MRE-binding affinity of MTF-1 by zinc is necessary for activation of Mt gene expression, it is not sufficient for zinc induction of gene expression in vivo (Smirnova et al 2000). In addition, phosphorylation is essential for MTF-1 transactivation in response to zinc and cadmium ions, and is controlled by a complex kinase signal transduction pathway that includes protein kinase C (PKC), phosphoinositide 3-kinase (PI3K), c-Jun N-terminal kinase, casein kinase-2 (CK2), Phosphatase and TENsin homolog (PTEN), protein phosphatase 2A (PP2A), and a protein tyrosine kinase (LaRochelle et al 2001;Saydam et al 2002;Lin et al 2012;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also, megalin intervened take‐up of nephrotoxins as aprotinin, toxins, aminoglycosides, and chemotherapeutic agents . Moreover, megalin is a receptor for the Proximal Tubular Endothelial Cell (PTEC) take‐up of heavy metal complexes through binding of its transporter (protein metallothionein) . The first rise in biomarker elimination proposes that megalin dysfunction may be timely indicator of AKI .…”
Section: Introductionmentioning
confidence: 99%
“…[15] Moreover, megalin is a receptor for the Proximal Tubular Endothelial Cell (PTEC) take-up of heavy metal complexes through binding of its transporter (protein metallothionein). [16] The might cause tubulointerstitial damage in several pathogenic situations by persuading oxidative stress. [20] Megalin has been branded as the vital molecule in the commencement of the pathogenic progression of endocytosis-mediated PTEC damage.…”
Section: Introductionmentioning
confidence: 99%